Log in to add a comment

## Answers

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

3/4 ( 7x- 1) - (2x - 1 - x/2) = x + 3/2

21x/4 - 3/4 - 2x + 1 + x/2 = x + 3/2

21x/4 - 2x + x/2 - x = 3/2 + 3/4 - 1

(21x-8x+2x-4x)/4 = (6+3-4)/4

11x/4 = 5/4

11x = 5

x = 5/11

21x/4 - 3/4 - 2x + 1 + x/2 = x + 3/2

21x/4 - 2x + x/2 - x = 3/2 + 3/4 - 1

(21x-8x+2x-4x)/4 = (6+3-4)/4

11x/4 = 5/4

11x = 5

x = 5/11

**3/4(7x-1)-(2x-1-x/2)=x+3/2 (given)**

**or,3(7x-1)-4(2x-1-x/2)=4(x+3/2) (multiplying both sides by 4 ,the least common denominator of 3/4 , 1 and 3/2)**

**or,21x-3-8x+4+2x=4x+6 (by simplification)**

**or,21x-8x+2x-4x=6+3-4 (taking the constants on one side and the variables on the other and reversing their respective symbols)**

**or,11x=5(by simplification)**

**or,x=5/11 ( dividing both sides by 11)**

**Ans:x=5/11.**